Percutaneous closure of patent foramen ovale and atrial septal defect - Rojko, Maja (Zdravniški vestnik, 2019)
A 67-year old man with a haemodynamically significant type secundum atrial septal defect (ASD), large patent foramen ovale (PFO) and a significant septal aneurism presented with shortness of breath and limited exercise tolerance. There was no evidence of additional structural abnormalities or significant coronary artery disease. Simultaneous percutaneous closure of both defects was planned. Since the wire could only be passed through PFO while the second wire could not be passed through the ASD, only PFO was closed with a 35 mm Amplatz PFO occluder. After 3 months, which served for tissue ingrowth of Amplatz PFO occluder and aneurism stabilization, ASD located in the posterior-inferior part of the fossa ovalis documented by three-dimensional transesophageal echocardiography (3D-TEE) was easily crossed and successfully closed with a 12 mm Amplatz ASD occluder. Stable position without unwanted interference between the devices was obtained. There was no residual shunting on colour Doppler and no bubble shunting during Valsalva maneuver. Within 6 months after the procedure, symptoms significantly improved and the right heart chambers decreased. 3D-TEE revealed both devices in good position with only trivial shunting through the PFO occluder documented by colour Doppler.
Keywords: atrial septal defect; odprto ovalno okno; okvara medpreddvornega pretina; patent foramen ovale; percutaneous closure; perkutano zapiranje